A poisonous cocktail: ethnic quotas, liberal voting rights and the democracy problem. Issue 3 (3rd April 2023) - Bochsler, Daniel
ABSTRACT: The literature on consociational democracies has introduced an important distinction between corporate and liberal types of consociations. However, once we apply a deeper conceptualization of this corporate-liberal divide, we find that many empirical cases are mixing elements of the two. Most consociational democracies of the corporate type rely on ethnic quotas or reserved seats for national elections, but combine them with liberal voting rights, i.e. a ballot that is universal for all voters, without segmenting voters into different identity groups. This has consequences for the democratic principle of "one-person-one-vote, " leading to a novel type of deviation. This article discusses different consociational democracies in light of the one-person-one-vote principle, and identifies new "paradoxes" of representation related to (corporate) quota rules that are combined with (liberal) universal voting rights.